Evaluation of the QTc internal and QT dispersion in patients with newly detected clinical hypothyroidism - N., Aravind G.; R., Archita (International Journal of Advances in Medicine, 2019)
Background: Thyroid hormones play an important role in the orchestration of various metabolic functions in the body and thus thyroid dysfunction can produce dramatic cardiovascular effects. Electrocardiographic changes such as bradycardia, low voltage complexes, and varying degrees of heart block are commonly recognized in hypothyroid patients. Hypothyroidism has been found to be associated with increased cardiovascular morbidity and mortality. Hence, it is important to investigate the ECG profile in these patients. The present study was aimed at evaluating the QTc interval and QT dispersion, an indicator of inhomogeneity of ventricular repolarisation and cardiac autonomic modulation in patients with newly detected clinical hypothyroidism. Methods: 50 patients with newly detected clinical hypothyroidism and 50 healthy controls were included in the study. The ECG was recorded and the heart-rate, QTc interval and QT dispersion were calculated. Results: The mean heart-rate was found to be significantly (p <0.05) reduced in hypothyroid patients when compared to healthy controls. The mean QTc interval and QT dispersion were significantly increased in hypothyroid patients when compared to controls. QTmin and QTmax of cases and controls also showed a statistically significant difference. Conclusion: Thus, the present study confirms the role of thyroid hormones on the cardiovascular system, particularly on ventricular repolarisation and cardiac autonomic modulation. Hence, early and prompt therapy with levothyroxine may help to prevent the adverse events resulting from cardiovascular dysfunction.